Surgical repair of orocutaneous fistula in the left submandibular region of a day-old calf with ectopic incisors - Munif, Mohammad Raguib (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: This study focuses on the orocutaneous fistula (OCF), a pathological channel between the buccal cavity and the outer surface (skin) of the face, causing leakage of saliva and fluid from the oral cavity to the face externally and also the ectopic incisors (EIs) erupted in a rare position in a day-old calf. The surgical interventions for these congenital defects were further described in this study. Materials and Methods: The calf was presented with an abnormal and external opening in the left submandibular region, having congenitally exposed jawbone and muscles with the resemblance of a linear groove, and was clinically examined based on the problem of swallowing milk due to lateral passing out of liquid through the unnatural tract before entering into the digestive tract. Clinical observation revealed an OCF with four EIs that abnormally erupted in the externally exposed groove of the fistula. Reconstructive surgery (RS) was performed along with a thorough guided approach to repair the defect, emphasizing normal functionality of the buccal cavity connecting to the pharynx and cranial esophagus, and smooth extraction of the EIs was ensured without making any deep wound. Results: After 2 weeks of postoperative care with supportive medications, the calf was quite recovered, having no further complications in the submandibular region along with no visible defect in swallowing. Conclusion: OCF in calves can be fruitfully treated by RS before getting severely infected and complicated. Outside the oral cavity, submandibular EIs can be easily removed, ensuring no further bleeding and defect. J. Adv. Vet. Anim. Res., 9(3): 509–515, September 2022 http://doi.org/10.5455/javar.2022.i620